The 'farm to plate' approach to food safety - Everyone's business - Allard, Denis G (Pulsus Group Inc, 2002)
Food safety is growing in importance as a public health concern for health practitioners and the general public. The Canadian public is exposed more extensively than ever before to exotic foods and pathogens via international travel, changing lifestyles and domestic contact with fresh foodstuff that is imported from faraway lands. Global warming, changing microbial ecology and resistance, and reduced host immunity are also having their effect in increasing the risk. To manage the risk adequately, interventions must be implemented at every point of the food supply chain, from production and processing to distribution, preparation and consumption, at home and in retail food service establishments. The role of government is explained, and the roles of other stakeholders, including physicians, are reviewed briefly.